Analysis of motor coordination alteration after anterior cruciate ligament reconstruction - Jurevièiene, V.; Kiele, D.; Jurevièius, R.; Èesnaitis, T. (Education. Physical training. Sport, 2012)
Research background and hypothesis. The Anterior cruciate ligament (ACL) is the most commonly injured ligament of the knee and its injuries result in significant functional impairment. Injury to the ACL is associated with altered knee joint loading and impaired neuromuscular control, which defined as the ability to produce well controlled movements and dynamic balance. Research aim. The aim of this study was to evaluate motor coordination and functional capacity of patients who received rehabilitation program following ACL reconstruction. Research methods. The study included 15 males aged 33.7 ± 2.49 years who had undergone unilateral ACL reconstruction with a semitendinosus/gracilis (STG) graft in Kaunas Clinical hospital. For objective functional testing, we used figure-of-eight movement coordination test. The Lysholm questionnaire was included as a disability outcome measure following ACL injury and reconstruction. The patients were assessed preoperatively and after 5 and 21weeks postoperatively. Research results. The results of this study indicated that motor coordination timescale showed significant differences (p < 0.05) between the injured and the healthy legs before surgery and after 5 and 21 weeks. The movement coordination test data showed that there the timescale significantly longer on the injured knee compared with the noninjured knee. After 21 weeks of rehabilitation we found significantly lower (p < 0.05) values in injured knees compared with the preoperative data. In injured knee the timescale after 21 weeks of rehabilitation was significantly (p < 0.05) longer compared with noninjured knee. The Lysholm questionnaire scale indicated that there was a significant difference in the results for values (p < 0.05) before surgery and after 21 weeks of rehabilitation. The questionnaire scale data showed that after 21 weeks of rehabilitation results for values was significantly (p < 0.05) highest compared with before surgery and after 5 weeks. Discussion and conclusions. There was improvement in the injured leg in mean motor coordination timescale 21 weeks after ACL reconstruction, but the timescale was higher than in the uninjured leg. After 21 weeks of ACL reconstruction knee functional status in most patients was good or excellent.